Local and Systemic Effect of Cytokinins on Soybean Nodulation and Regulation of Their Isopentenyl Transferase (IPT) Biosynthesis Genes Following Rhizobia Inoculation - Mens, Celine; Li, Dongxue; Haaima, Laura E.; Gresshoff, Peter M.; Ferguson, Brett J. (Frontiers in Plant Science, 2018)
Cytokinins are important regulators of cell proliferation and differentiation in plant development. Here, a role for this phytohormone group in soybean nodulation is shown through the exogenous application of cytokinins (6-benzylaminopurine, N6-(Δ2-isopentenyl)-adenine and trans-zeatin) via either root drenching or a petiole feeding technique. Overall, nodule numbers were reduced by treatment with high cytokinin concentrations, but increased with lower concentrations. This was especially evident when feeding the solutions directly into the vasculature via petiole feeding. These findings highlight the importance of cytokinin in nodule development. To further investigate the role of cytokinin in controlling nodule numbers, the IPT gene family involved in cytokinin biosynthesis was characterised in soybean. Bioinformatic analyses identified 17 IPT genes in the soybean genome, and homeologous duplicate gene partners were subsequently identified including GmIPT5 and GmIPT6, the orthologues of LjIPT3. Expression of GmIPT5 was upregulated in the shoot in response to nodulation, but this was independent of a functional copy of the AON receptor, GmNARK, which suggests it is unlikely to have a role in the negative feedback system called autoregulation of nodulation (AON). Legumes also control nodule numbers in the presence of soil nitrogen through nitrate-dependent regulation of nodulation, a locally-acting pathway in soybean. Upon nitrate treatment to the root, the tandem duplicates GmIPT3 and GmIPT15 were upregulated in expression indicating a role for these genes in the plant’s response to soil nitrogen, potentially including the nitrate-dependent regulation of legume nodulation pathway. Additional roles for cytokinin and their IPT biosynthetic genes in nodulation and the control of nodule numbers are discussed.